2015
DOI: 10.1162/jocn_a_00868
|View full text |Cite
|
Sign up to set email alerts
|

The Basis for Language Acquisition: Congenitally Deaf Infants Discriminate Vowel Length in the First Months after Cochlear Implantation

Abstract: One main incentive for supplying hearing impaired children with a cochlear implant is the prospect of oral language acquisition. Only scarce knowledge exists, however, of what congenitally deaf children actually perceive when receiving their first auditory input, and specifically what speech-relevant features they are able to extract from the new modality. We therefore presented congenitally deaf infants and young children implanted before the age of 4 years with an oddball paradigm of long and short vowel var… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
15
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 49 publications
3
15
0
1
Order By: Relevance
“…We therefore assume that in our group the long absence of any auditory stimulation causes but a brief delay in catching up with normal hearing peers. That would be in line with our findings on the processing of vowel duration, where congenitally deaf children display ERPs equivalent to their normal hearing peers already after 2 months of implant use (Vavatzanidis et al, 2015 ).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…We therefore assume that in our group the long absence of any auditory stimulation causes but a brief delay in catching up with normal hearing peers. That would be in line with our findings on the processing of vowel duration, where congenitally deaf children display ERPs equivalent to their normal hearing peers already after 2 months of implant use (Vavatzanidis et al, 2015 ).…”
Section: Discussionsupporting
confidence: 92%
“…As to the longer duration, we were able to show that congenitally deaf children need only 2 months of hearing experience with the implant to differentiate between short and long vowel durations. After 4 months, they have already reached the level of normal hearing peers (Vavatzanidis et al, 2015 ). We can thus conclude that at least one prerequisite for the perception of stress pattern is available to the children soon after implantation.…”
Section: Introductionmentioning
confidence: 99%
“…In our study, improvements in behavioural electrode discrimination were accompanied by an increase in spatial ACC amplitude over the first 6 months of CI use. Whilst changes in the spatial ACC over time have not been previously reported, a number of studies have assessed longitudinal changes in discrimination ability in CI users using MMN measurements (Lonka et al, 2013(Lonka et al, , 2004Purdy and Kelly, 2016;Vavatzanidis et al, 2015). In general, these studies have shown an increase in MMN amplitude with CI experience but in most cases the MMN could not be recorded in the early period after switch-on.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Because our knowledge of and discourse around how spoken language develops among d/hh children and the availability of technologies that may support access to speech have both changed dramatically in recent years, this review focuses only on the research published on this topic within the last 20 years. Among studies of language acquisition after cochlear implantation, study designs and salient participant demographics vary widely from longitudinal case studies of a single child [43], to short-term investigations with multiple children [44]. Some studies focus on participant language development from as early as seven months old [45], while others investigate the period immediately after implantation or several years after implantation up to ages 10-15 [20].…”
Section: Spoken Language Development and Instructionmentioning
confidence: 99%